A szegénység dinamikája - MitevPetar-Emil; Holló, István; Hegedűs, Rita (Szociológiai Szemle, 2024)
The research basis is provided by the project Poverty, Ethnicity, Gender in Transitional Societies implemented under the leadership of Professor Iván Szelényi in six countries of the former Eastern block in 1999-2000. The data have confirmed the initial assumption of the study: new poverty is being born, which is not an element of the life cycle of the individual but rather a socio-economic dependence affecting entire groups of people. The socio-biological factors (age, gender, children) are not pushed away but are rather transformed by the new dominant. The new socio-economic context even reinforces their effect, especially in some countries. A new, unexpected phenomenon is the formation of an age underclass in Southeast and Russia. All the countries surveyed, except for Poland, exhibit symptoms of poverty feminization. The number of children in a family is a primordial factor bearing on the family budget. However, the strongest dependence is ethnicity-based. The poverty of Roma in Southeast Europe is catastrophic and separates them into an ethnic underclass. Roma people in Hungary are losers as well but their poverty has a different macro-economic backdrop. The differentia specifica of the research topic itself: it is not a static situation but a process in which reason and effect change places, a process that both shapes and is affected by the social structure. In parallel to the liberalization of economic initiative, powerful destructive processes are under way that tear the old social connections apart and turn the social status of immense groups of people upside down. The former middle layers are layered further. The income below average is the common denominator for many of them (in Central Europe) or for the majority (Southeast Europe and Russia), in contrast to the average income before. It could be foreseen that poverty will be irreversible for many and would entail declassation. This is already a fact for ethnic minorities in Southeast Europe and for elderly people there and in Russia. The further dynamics of the process could be traced at a new stage of the study.